Changes in Oral Health Knowledge Baseline DMFT Status Among Pregnant Women at a Primary Healthcare Center - I Gusti Agung Ayu Chandra Iswari Dewi; Gusti Ayu Yohanna Lily; I Gusti Ayu Ratih Pramesti; I Wayan Agus Wirya Pratama; I Gede Irvan Pratama (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Oral health education may improve maternal knowledge, while baseline oral health status reflects existing treatment needs. This study evaluated changes in oral health knowledge following oral health education according to educational level and described baseline Decayed, Missing, and Filled Teeth (DMFT) status among pregnant women. Materials and Methods: A pre-experimental one-group pretest-posttest study was conducted among 15 pregnant women attending Puskesmas IV South Denpasar, Bali, Indonesia, in November 2025. Oral health knowledge was assessed using a researcher-developed 15-item multiple-choice questionnaire administered before and immediately after the intervention. The Shapiro–Wilk test was used to assess normality, and differences between pretest and posttest knowledge scores were analyzed using the Wilcoxon signed-rank test. Effect size was calculated using r = Z/√N. Results and Discussion: The median knowledge score increased from 73.3 before the intervention to 80.0 after oral health education. The improvement was statistically significant (Z = −2.81; p = 0.005) with a large effect size (r = 0.73). Participants with higher educational attainment achieved higher posttest knowledge scores. The mean DMFT score was 4.4 ± 1.7, with untreated decayed teeth representing the predominant component. Conclusion: Oral health education significantly improved pregnant women's oral health knowledge. However, untreated dental caries remained prevalent, highlighting the importance of integrating oral health education with routine oral screening and preventive dental care within antenatal healthcare services. Results: The median knowledge score increased from 73.3 before the intervention to 80.0 after oral health education. The improvement was statistically significant (Z = −2.81; p = 0.005) with a large effect size (r = 0.73). Participants with higher educational attainment achieved higher posttest knowledge scores. The mean DMFT score was 4.4 ± 1.7, with untreated decayed teeth representing the predominant component. Conclusion: Oral health education significantly improved pregnant women's oral health knowledge. However, untreated dental caries remained prevalent, highlighting the importance of integrating oral health education with routine oral screening and preventive dental care within antenatal healthcare services